PERSEPSI GENERASI Z TERHADAP TRANSFORMASI DIGITAL DALAM ADMINISTRASI PERPAJAKAN - Surianto, Nurul Maghfirah; Azisah, Andi Nurul (Universitas Islam Negeri Alauddin Makassar, 2026)
This study seeks to examine Generation Z’s perceptions of digital transformation in tax administration and to identify the factors influencing these perceptions along with their implications for tax awareness. A qualitative descriptive approach was employed through in-depth interviews involving three informants, namely a Diploma IV Accounting student, a Master’s degree Accounting student, and Generation Z taxpayers. The participants were selected using purposive sampling, while the data were analyzed through an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that Generation Z generally holds positive perceptions toward the digitalization of tax services, as these systems provide greater convenience, efficiency, and flexibility in the tax reporting process.However, obstacles remain, such as system disruptions, limited internet access, and low tax literacy. The digitalization of tax services has the potential to increase tax awareness, but needs to be supported by adequate education. Therefore, improving the quality of the system and developing a more effective tax education strategy are crucial to supporting the optimization of digital tax services for Generation Z